2015
DOI: 10.15408/ess.v4i2.1965
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Komitmen Profesional Dan Sosialisasi Antisipatif Mahasiswa Audit Terhadap Perilaku Whistleblowing

Abstract: This study examines the anteceden of whistleblowing behavior by the professional commitment and anticipatory socialization student audit. It's extend Elias (2008) and criticizes on the mismatch between the hypothesis with testing tools are used, so that the results can't answer hypothetical appropriately. The used data is 104 of accounting students who have taken the course of auditing. Hypothesis testing used multiple regression test and t-test, with the previous factor analysis. The result indicates that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
2
2
1
4
Order By: Relevance
“…In a study conducted by Elias (2008), he found that one's anticipatory socialization influences his intention to do whistleblowing. However, it is different from the results obtained by Jalil (2014), in which the anticipatory socialization does not influence one's intention to do whistleblowing. Furthermore, there are also gender differences that can influence someone in terms of decision making, orientation, and evaluation which require moral and ethical considerations (Loo, 2002).…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Elias (2008), he found that one's anticipatory socialization influences his intention to do whistleblowing. However, it is different from the results obtained by Jalil (2014), in which the anticipatory socialization does not influence one's intention to do whistleblowing. Furthermore, there are also gender differences that can influence someone in terms of decision making, orientation, and evaluation which require moral and ethical considerations (Loo, 2002).…”
Section: Introductioncontrasting
confidence: 99%
“…Elias (2008) concludes that the higher the level of anticipatory socialization, the higher one's tendency to do whistleblowing. However, different results are shown in a study by Jalil (2014) in which anticipatory socialization does not influence one's actions to do whistleblowing. The same thing happened with the results obtained by Mela et al (2016) where there is no significant influence between anticipatory socialization and the intention of auditing students to do whistleblowing.…”
Section: Professional Commitmentmentioning
confidence: 69%
“…Dalam menjalankan tugasnya, auditor profesional harus berperilaku etis sesuai dengan etika profesi yang ditetapkan oleh Institut Akuntan Publik Indonesia (IAPI). Jalil (2014), menyatakan bahwa perilaku etis auditor merupakan penentuan reputasi dan kredibilitas atas profesinya di bidang akuntansi.…”
Section: Pendahuluanunclassified
“…Pelaporan whistleblowing dapat dilakukan secara internal maupun eksternal. Jalil (2014), menyatakan bahwa whistleblowing internal adalah pelaporan yang dilakukan oleh individu dalam suatu organisasi atas tindak penyelewengan yang tidak etis kepada pihak manajemen. Sedangkan, whistleblowing eksternal merupakan pelaporan yang dilakukan oleh individu dalam suatu organisasi atas perilaku kecurangan yang tidak etis kepada pihak eksternal organisasi maupun penegak hukum.…”
Section: Pendahuluanunclassified
“…Whereas situational factors are factors exist around individuals that supports someone to conduct whistleblowing. Both of these factors lead to many independent variables including professional commitment, anticipatory socialization, personal costs, attitudes, organizational commitment, level of seriousness of the problem, professionalism, materiality errors, ethical orientation, ethical sensitivity, gender, academic performance, level of education (O'Leary and Cotter, 2000;Crismastuti, 2008;Akbar, 2009;Rahadian, 2010;Ghani, 2010;Risti, 2012;Olawale, 2012;Winardi, 2013;Jalil, 2014;Bagustianto, 2014;Devi, 2014;Samudera, 2014;Rustiarini, 2015;Dimas, 2015;Sudibyo and Mirna, 2016). Most of the previous researches measure variables by using normative questionnaires.…”
Section: Introductionmentioning
confidence: 99%